Design and synthesis of dual-active heterocyclic yybrid inhibitors for β-Hematin and plasmodium falciparum N-Myristoyltransferase - Hay, Jonathan Bruce (Stellenbosch : Stellenbosch University, 2016)
Thesis (MSc)--Stellenbosch University, 2016.